Guaranteed Time Slot Allocation for IEEE 802.15.4-Based Wireless Feedback Control Systems - Kentaro Kobayashi; Hiraku Okada; Masaaki Katayama (IEEE Access, 2019)
In this paper, wireless feedback control of multiple machines over a beacon-enabled IEEE 802.15.4 network is considered. In the beacon-enabled IEEE 802.15.4 network, beacons periodically structure superframes on the time axis, and each superframe consists of a contention access period (CAP) and a contention free period (CFP). In the CAP, a carrier sense multiple access/collision avoidance (CSMA/CA) is used; in the CFP, a guaranteed time slot (GTS)-based time division multiple access is used. Because of collision and backoff periods of packet transmission, the probability of communication failure in the CAP is greater than that in the CFP; however, the number of available GTSs is limited to seven by the standard. In order to improve the control performance of wireless feedback control, the controller must effectively allocate GTSs to transmit control input and state feedback of controlled machines. We provide a simple but efficient idea that takes both the feedback control mechanism and packet transmission mechanism of the CAP and CFP into consideration to better allocate GTSs. We propose a superior GTS allocation method that fully conforms to the IEEE 802.15.4 standard and show that the proposed method can further improve control performance.